Black children of incarcerated parents speak truth to power: social revolution - Gatewood, Britany Jenine; Muhammad, Bahiyyah Miallah; Turner, Sydni Myat (Routledge, 2024)
"This book centers directly impacted Black children who have lived through parental incarceration. Their stories are told from holistic perspectives incorporating the full range of collateral consequences. Shifting from the Eurocentric and capitalistic viewpoint, they move us beyond negative outcomes to a positive prism by providing insider perspective, strategy, advice, and compelling experiences. We center Black children of incarcerated parents (BCOIP) rich narratives to show how they are conscious thinkers with perspectives that can help reimagine all Black children's lives and futures. These stories help readers better understand the importance of exploring the revolutionary ways BCOIP continue to survive, thrive, and transform amid the dynamic challenges surrounding mass incarceration. The book shifts the social dialogue from fear of intergenerational crime and incarceration to resilience, success, Black joy, and self-love, and moves from sympathetic into an empathetic agenda. The book brings to the forefront counter storytelling through oral narratives that fill a gap in literature that leaves out the voices of children of incarcerated parents who are doctors, lawyers, professional athletes, musicians, community leaders, activists, professors, teachers, best-selling authors and much more. These are vital experiences to share because not all BCOIP will end up in prison, jail, or a detention centre. Black Children of Incarcerated Parents Speak Truth to Power will be of great interest to scholars from the humanistic social sciences and humanities. It is also a timely resource for students (high school, undergraduate and graduate) in sociology, criminology, corrections, humanities, social work, counselling, education, social justice, and related courses, as well as agency administrators, community organizations servicing families of the incarcerated, specifically incarcerated parents and the children of incarcerated parents, themselves"--